2017
DOI: 10.1002/chem.201605303
|View full text |Cite
|
Sign up to set email alerts
|

AuI Iminophosphorane Complexes as Efficient Catalysts for the Cycloisomerization of Alkynyl Amides under Air, at Room Temperature, and in Aqueous or Eutectic‐Mixture Solutions

Abstract: New iminophosphorane-phosphine Au complexes [AuCl(κ -P-Ph PCH P{=NP(=S)(OR) }Ph )] (3 a,b) and [Au Cl (μ -P,S-Ph PCH P{=NP(=S)(OR) }Ph )] (4 a,b) proved to be general, very efficient, and recyclable (up to four consecutive runs) catalysts for the cycloisomerization of alkynyl amides in water or choline chloride-based eutectic mixtures as green solvents. Remarkably, this cycloisomerization reaction took place under mild conditions (low catalyst loading, at room temperature, and in the absence of cocatalysts or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…We observed conversions higher than 70% with some of these gold complexes (see Supplementary Table 1 ), which confirm the viability of achieving the gold-catalyzed process in water, in absence of scavenging additives. The direct use of gold chloride catalysts in aqueous solvents has few precedents, none of them studying the activating role of water as a formal chloride scavenger 32 39 . To shed some light on this water-promoted activation process, we performed a series of NMR and ESI-MS studies (detailed in the Supplementary Note 7 ) which confirmed that water facilitates the ionization of the Au–Cl bond, and thereby triggers the reactivity of the gold complexes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed conversions higher than 70% with some of these gold complexes (see Supplementary Table 1 ), which confirm the viability of achieving the gold-catalyzed process in water, in absence of scavenging additives. The direct use of gold chloride catalysts in aqueous solvents has few precedents, none of them studying the activating role of water as a formal chloride scavenger 32 39 . To shed some light on this water-promoted activation process, we performed a series of NMR and ESI-MS studies (detailed in the Supplementary Note 7 ) which confirmed that water facilitates the ionization of the Au–Cl bond, and thereby triggers the reactivity of the gold complexes.…”
Section: Resultsmentioning
confidence: 99%
“…In many cases the reactions can be carried out using gold(I) chlorides, but they require the addition of chloride scavengers such as silver(I) salts to replace chloride by a more labile ligand. Curiously, some isolated reports on gold-promoted transformations in water, developed in the context of green chemistry, suggest that in this solvent such scavengers might not be strictly needed 32 39 . This is particularly relevant when one envisions to translate the power of gold catalysis to biologically relevant aqueous environments, and eventually, to native cellular settings.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the indole compound 2 m was easily constructed through this cycloisomerization with 75% yield, which provided an efficient synthetic method to prepare indole (Scheme b). In addition, it is very challenging to produce seven or eight‐membered lactams through the metal‐catalyzed cycloisomerization of alkynyl amides . The alkynyl amide substrate 2‐(but‐3‐yn‐1‐yl)‐N‐tosylbenzamide 1 n was then examined in this Ir‐catalyzed cycloisomerization, the desired product seven‐membered unsaturated lactam 2 n could be obtained but with 18% yield (Scheme c).…”
Section: Figurementioning
confidence: 99%
“…Acetylation of monosaccharides in ChCl-ZnCl 2 (1:2), shown for α-1-methoxyglucose. Other transformations catalyzed by transition metals are the hydroformylation of 1-decene in cyclodextrin-DMU catalyzed by Rh [160] and the cycloisomerization of γ-alkynoic acids, [161] (Z)-enynols, [162] and alkynyl amides [163] in ChCl-based DES catalyzed by Au I . [125] However, the sensitivity of these chloroaluminate ILs to water may lead to deactivation.…”
Section: Application In Organic Synthesismentioning
confidence: 99%